“Ser” como interpretación de la realidad - Seguró, Miquel (Sapientia, 2008)
In our context of discrediting of Metaphysics, José Gómez Caffarena offers a reflection speculative which, steeped in the human, look for to ‘say’ so truthful and relevant essence of the structure last of the real. To do it exposes an ontology that, based on a transcendental methodology, aims to achieve a Metaphysics of being that respects both the limits of what is phenomenal as the pretence of truth from which it is done. This paper discusses the viability of this latest proposal precisely because it would mean their ability to go beyond what the method allows.